Optimasi Campuran Aspal Lapis Aus (AC-WC) melalui Substitusi Ban Bekas dan Additive Anti-Striping - Febriansyah, Dinar; Firdaus, Firdaus (Jurnal Talenta Sipil, 2025)
Used vehicle inner tire waste is natural rubber that has gone through a manufacturing process and has gone through the addition of certain mixtures and then molded into the form of inner tires for motorized vehicles. Used motor vehicle inner tires come from various materials such as natural rubber, synthetic rubber, chemicals, carbon black and certain oils. The properties of rubber are that it is strong and flexible or elastic. The remains of these used vehicle inner tires can be used as additional material for the wear layer mixture (AC-WC). The aim of this research is to determine the effect of using used tires on the wear layer mixture (AC-WC). The research method involves the preparation of several AC-WC asphalt mixtures with varying ratios of used tire powder and the addition of anti-tiping additives. The resulting asphalt mixture is then tested using various laboratory tests, including stability, durability and density tests, voids in the mixture (VIM), air voids in the mix (VMA), voids filled with asphalt melting asphalt (VFA). Based on the results of Marshall parameter testing in terms of variations in used tire substitution, it can be concluded that the influence of the stability value on optimum tire rubber lies in the percentage at 2%, because at that time the Marshall stability value increased by a value of 1130 kg compared to the stability value without additives. 1102 kg Meanwhile, the density value is 2.322 gr/cc, VIM is 3.70%, VMA is 16.72%, VFA is 79.36%, flow is 3.31 mm. Marshall remaining 91.67